Length-Dependent Prolongation of Force Relaxation Is Unaltered by Delay of Intracellular Calcium Decline in Early-Stage Rabbit Right Ventricular Hypertrophy - Monasky, Michelle M.; Torres, Carlos A. A.; Janssen, Paul M. L. (Frontiers in Physiology, 2017)
Chronic pressure overload can result in ventricular hypertrophy and eventually diastolic dysfunction. In normal myocardium, the time from peak tension to 50% relaxation of isolated cardiac myocardium is not directly determined by the time for calcium decline. This study aims to determine whether the time for calcium decline is altered with a change in preload in early-stage hypertrophied myocardium, and whether this change in time for calcium decline alters the rate of relaxation of the myocardium. Young New Zealand white rabbits underwent a pulmonary artery banding procedure and were euthanized 10 weeks later. Twitch contractions and calibrated bis-fura-2 calcium transients were measured in isolated thin right ventricular trabeculae at optimal length and with the muscle taut. Systolic calcium, calcium transient amplitude, and time from peak tension to 50% relaxation all increased with an increase in preload for both hypertrophied and sham groups. Time for intracellular calcium decline increased both with an increase in preload and an increase in extracellular calcium concentration in hypertrophied myocardium but not in sham, while time from peak tension to 50% relaxation did not significantly change between groups under either condition. Also, time for intracellular calcium decline generally decreased with an increase in extracellular calcium for both hypertrophied and sham groups, while time from peak tension to 50% relaxation generally did not significantly change in either group. Combined, these results indicate that the mild hypertrophy significantly changes calcium handling, but does not impact on the rate of force relaxation. This implies that the rate-limiting step in force relaxation is not directly related to calcium transient decline.